Rare opportunistic mycoses in cats: phaeohyphomycosis and hyalohyphomycosis: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Lloret, Albert; Hartmann, Katrin; Pennisi, Maria Grazia; Ferrer, Lluis; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hosie, Margaret J; Lutz, Hans; et al.
Overview: Phaeohyphomycoses and hyalohyphomycoses are rare opportunistic infections acquired from the environment. More cases have been reported in recent years in humans and cats. Disease signs: Single or multiple nodules or ulcerated plaques (which may be pigmented) in the skin are the typical lesions. In some cases the infection disseminates or involves the central nervous system (CNS). Diagnosis: Diagnosis is based on fungal detection by cytology and/or histology. Culture provides definitive diagnosis and species identification. Treatment: Treatment involves surgical excision in cases of localised skin disease followed by systemic antifungal therapy, with itraconazole as the agent of first choice. Relapses after treatment are common. Itraconazole and other systemic antifungal agents have been used to treat systemic or neurological cases, but the response is unpredictable. The prognosis is guarded to poor in cats with multiple lesions and systemic or neurological involvement. Zoonotic risk: There is no zoonotic risk associated with contact with infected cats.